Understanding Mental Health Challenges in the Elderly: Insights from the Self-Reporting Questionnaire (SRQ) at Sempaja Healthcare Center - Rahayu, Hanis Kusumawati; Cicilia Yolanda, Sihombing; Mursen, Husnul Khatimah; Kurniansyah Jayadi, Aditya; Fitriany, Evi; Pramulia Yudia, Riries Choiru; Ariani, Emma (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Indonesia's aging population is expanding rapidly, leading to a rise in elderly individuals confronting serious health challenges. The primary mental health issue in this group is excessive stress, which is often associated with emotional disorders, social isolation, and a reduced quality of life. To address this, the Ministry of Health of the Republic of Indonesia has established mental health screening policies to improve healthcare quality for the elderly. Nonetheless, further exploration of the prevalence and characteristics of mental health issues in this population is essential to inform effective interventions. Objectives: This study aims to offer an overview of mental health among the elderly within the Sempaja Healthcare Center's service area. Methods: A descriptive cross-sectional study was conducted using the Self-Reporting Questionnaire (SRQ) for data collection. Consecutive sampling was applied, resulting in a sample size of 99 elderly participants. The SRQ identified symptoms of mental health disorders, and the data were analyzed to assess the prevalence and characteristics of these mental health concerns. Results: Among the 99 participants, 40 elderly participants were identified as having mental health issues. Most elderly individuals with mental health disorders experienced emotional disorders (42.5%), with the majority in the 60–74 age group (90%), female (55%), having completed primary education (45%), unemployed (72.5%), and married (70%). These findings indicate that certain demographic groups are more vulnerable to mental health challenges. Conclusions: This study emphasizes the importance of the need for targeted mental health screenings and interventions for the elderly, especially among high-risk groups. Strengthening mental health services and promoting educational programs that address stress management and social support may significantly improve the well-being and quality of life of elderly individuals through mental health screening and addressing mental health issues among the elderly population.